Biodiesel stabilization by dibrominated dimethoxybenzaldehydes: a comprehensive computational perspective - Borges, Igor D.; Aguiar, Antônio S. N.; Camargo, Ademir J.; Napolitano, Hamilton B. (Frontiers in Chemical Engineering, 2026)
The oxidative instability of biodiesel remains a critical barrier to its widespread adoption despite its advantages as renewable, biodegradable, and low-emission fuel. Antioxidant additives are an established strategy to suppress free radical chain reactions, yet their efficiency is strongly modulated by molecular structure and solvent environment. This is the first comparative density functional theory study of dibrominated dimethoxybenzaldehydes and standard phenolic antioxidants under biodiesel-relevant solvent conditions using the conductor-like polarizable continuum model. Frontier molecular orbitals, Fukui index, ionization potentials, spin density distributions, and natural bond orbital hyperconjugations were systematically analyzed across polar and nonpolar environments. The computational results suggest that bromination is associated with increased electronic softness and electron transfer potential, while also leading to changes in the stability of radical intermediates, especially in ortho-substituted derivatives. Among the dibrominated compounds, IB1 exhibits the most balanced combination of computed properties, whereas IB3, although highly reactive in silico, is predicted to form comparatively less stable radical species. Compared with commercial benchmarks, these halogenated systems constitute a distinct mechanistic class governed by polarization rather than hydroxyl-centered resonance. These computational findings provide guidance for the rational design of next-generation biodiesel stabilizers, pending future experimental validation.